The SME of Río Gallegos and Santa Cruz, their development, management control and incorporation of TIC over time (AACINI - International Journal of Industrial Engineering, 2023)
The present work, is a temporary analysis of the changes that the local and regional Santa Cruz SMEs have presented is carried out. The study is based on 3 instances carried out in different temporary spaces, through surveys andinterviews with qualified informants. Aspects related to human resource management, strategic planning, use of ICTs and effects of the Pandemic were analyzed. It is observed that some patterns have been sustained over time while some indicators related to human resources and the use of technology have increased.
Keywords: SME; HR; TIC; HREG